Systematic investigation of TetR-family transcriptional regulators and their roles on lignocellulosic inhibitor acetate tolerance in Zymomonas mobilis - Xiao, Yubei; Qin, Tongjia; He, Shuche; Chen, Yunhao; Li, Han; He, Qiaoning; Wang, Xia; Yang, Shihui (Frontiers in Bioengineering and Biotechnology, 2024)
TetR-family transcriptional regulators are widely distributed among bacteria and involved in various cellular processes such as multidrug and inhibitor resistance. Zymomonas mobilis is a industrial bacterium for lignocellulosic ethanol production. Although TetR-family regulators and their associated RND-family efflux pumps in Z. mobilis have been identified to be differentially expressed under various inhibitors and stressful conditions, there are no systematic investigation yet. In this study, bioinformatic analyses indicated that there are three TetR-family transcriptional regulators (ZMO0281, ZMO0963, ZMO1547) and two RND-family efflux pumps (ZMO0282-0285, ZMO0964-0966) adjacent to corresponding TetR-family regulators of ZMO0281 and ZMO0963 in Z. mobilis. Genetics studies were then carried out with various mutants of TetR-family regulators constructed, and ZMO0281 was characterized to be related to acetate tolerance. Combining transcriptomics and dual-reporter gene system, this study demonstrated that three TetR-family regulators repressed their adjacent genes specifically. Moreover, TetR-family regulator ZMO0281 might also be involved in other cellular processes in the presence of acetate. In addition, the upregulation of RND-family efflux pumps due to ZMO0281 deletion might lead to an energy imbalance and decreased cell growth in Z. mobilis under acetate stress. The systematic investigation of all three TetR-family regulators and their roles on a major lignocellulosic inhibitor acetate tolerance in Z. mobilis thus not only unravels the molecular mechanisms of TetR-family regulators and their potential cross-talks on regulating RND-family efflux pumps and other genes in Z. mobilis, but also provides guidance on understanding the roles of multiple regulators of same family in Z. mobilis and other microorganisms for efficient lignocellulosic biochemical production.